An experimental study on combustion and particulate emissions characteristics on a dual-injection gasoline engine. (25th June 2019) - Chen, Wenhao; Xia, Chun; Zhu, Lei; Mao, Kerang; Tao, Jie; Fang, Junhua; Huang, Zhen
Highlights: Dual-injection increases the peak of in-cylinder pressure curves and yields a notable CO reduction. Dual-injection can significantly reduce the PN emission compared to GDI engines. The peak of size distributions curves for dual-injection tends to shift towards the smaller diameter region. The soot particles from dual-injection have lower oxidation activation energy. Abstract: European standards have set stringent particulate number (PN) regulations for gasoline direct injection (GDI) engine, proposing a great challenge for the particulate emission control. The dual-injection mode, which incorporates direct-injection with port-fuel-injection, is considered to be an effective approach to reduce PN emissions. In this study the combustion, gaseous and particulate emission characteristics under different direct-injection ratios in a dual-injection gasoline engine were investigated. The results show that dual-injection increases the peak of in-cylinder pressure curves and makes the heat release curves shift towards an earlier region. The dual-injection mode yields a notable CO reduction while there is a slight increase in NOx emission. Dual-injection can significantly reduce the PN emission compared with GDI engines. As the direct-injection ratio decreases, the PN concentration continuously declines. The peak of size distributions curves for dual-injection tends to shift towards the smaller diameter region, showing the ability to generate particles in smaller size. The soot particles from dual-injection have lower oxidation activation energy than those from direct-injection. According to the results above, it can be inferred that dual-injection can promote the combustion process and has remarkably positive effects on particle emission control owing to its reduced PN emissions and improved particle oxidation reactivity.